2016
DOI: 10.1177/0036933015597174
|View full text |Cite
|
Sign up to set email alerts
|

Is estimated intra-operative blood loss a reliable predictor of surgical outcomes in laparoscopic colorectal cancer surgery?

Abstract: This study has shown that intra-operative blood loss was not associated with increased median length of stay nor did it increase the 30 day re-admission rate. However, increased intra-operative blood loss was associated with increased incidence of post-operative morbidity and risk of reoperation within 30 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
7
1
Order By: Relevance
“…Egenvall et al reported that larger IBL increases the risk of later surgery for small bowel obstruction caused by tumor recurrence and surgical complications, but OS was not affected ( 20 ). Another study also reported IBL was not associated with increased median length of hospital stay nor did it increase the 30-day readmission rate ( 19 ). However, other studies reported that larger IBL was associated with increased complications or poor prognosis ( 16 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Egenvall et al reported that larger IBL increases the risk of later surgery for small bowel obstruction caused by tumor recurrence and surgical complications, but OS was not affected ( 20 ). Another study also reported IBL was not associated with increased median length of hospital stay nor did it increase the 30-day readmission rate ( 19 ). However, other studies reported that larger IBL was associated with increased complications or poor prognosis ( 16 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that larger IBL could increase complications and reduce prognosis ( 16 18 ). However, other studies reported that IBL had no effect on complications and prognosis ( 19 , 20 ). Furthermore, no previous studies reported the intraoperative blood transfusion (IBT) on the outcomes and prognosis of patients with CRC.…”
Section: Introductionmentioning
confidence: 91%
“…Prevention strategies that aim to mitigate risk factors for complications following colorectal surgery are well described. [ 54 ] These include preoperative weight loss, [ 54 ] nutritional optimization through immunonutrition [ 55 ] and early postoperative enteric nutrition, [ 56 ] intraoperative blood loss and blood transfusion minimization, [ 57 , 58 ] and use of laparoscopic surgery if feasible. [ 59 , 60 , 61 ] Incorporation of these strategies and others into enhanced recovery after surgery management programs has been shown to be associated with reduced postoperative complications, [ 60 ] reduced hospital LOS and costs.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that perioperative blood transfusion is associated with shortened long-term survival after cancer (including pancreatic cancer) surgery [36,37]. As a matter of fact, high volume intraoperative blood loss is also associated with worse outcomes including increased postoperative complications [38] and deteriorated long-term outcomes [39,40]. For example, in a retrospective study of patients with stage II/III gastric cancer, intraoperative blood loss of > 330 ml was associated with early recurrence after surgery [39].…”
Section: Discussionmentioning
confidence: 99%